Transcriptional Complexity of the HOXA9 Locus - Popovic, Relja (2007)
Evolutionarily conserved HOX genes play an important role during development and hematopoiesis. HOX protein products are transcription factors whose precise mechanism of action is still poorly understood. Regulation of HOX gene expression has been the topic of various studies. While alternative splicing and alternative promoter usage have been known to increase the number of transcripts across the HOX clusters, more recently high-throughput analyses have identified a number of new coding and noncoding RNA molecules whose function is not known. Here we review the transcriptome of the most studied HOX locus, HOXA9. Strict control of HOXA9 expression has been shown to play a critical role in hematopoiesis while aberrant expression has been shown important to the development of leukemia. However, it is still unclear how various transcripts from this locus are regulated and what specific role(s) each one of them plays.